Surface roughness and MRR effect on manual plasma arc cutting machining - Bhuvenesh, Rajamony, Assoc. Prof. Dr. (World Academy of Science, Engineering and Technology (WASET), 2012)
Link to publisher's homepage at http://www.waset.org/